COVID-19 and entrepreneurship: challenges and opportunities for small business - Ratten, Vanessa (London And New York: Routledge, 2021)
'Amid the COVID-19 pandemic, small businesses are especially vulnerable. This is one of the first books that explicitly examines the linkage between crisis and entrepreneurship with specific focus on small businesses. The book adopts a holistic approach and outlines strategies which small business owners can utilize and, as well as, business opportunities that are available in these new market conditions. It also provides a comparative analysis of the current and future market conditions to enable a better understanding of how institutional structures can facilitate or hinder growth. The book also goes on to explain why and how creativity and innovation can help to mitigate the impact of such crisis on business and highlights why business continuity is especially crucial to family owned businesses. This timely publication will help to guide small business owners and entrepreneurs to maintain business continuity and build up their resilience in challenging business climate'--
Includes bibliographical references and index.
Keywords: Small business; Crisis management; Entrepreneurship; COVID-19 (Disease) -- Economic aspects